A Transgenic Mouse Model to Selectively Identify α3 Na, K-ATPase Expressing Cells in the Nervous System. (1st February 2019) - Dobretsov, Maxim; Hayar, Abdallah; Kockara, Neriman T.; Kozhemyakin, Maxim; Light, Kim E.; Patyal, Pankaj; Pierce, Dwight R.; Wight, Patricia A.
Highlights: Transgenic mice have been generated that use the mouse Atp1a3 promoter to drive expression of ZsGreen1 fluorescent protein. ZsGreen1 fluorescent neurons are readily identifiable in both fixed and unfixed tissue from brain. The model provides a novel tool to elucidate the distribution and functional properties of α3 NKA-expressing neurons. Abstract: The α3 Na +, K + -ATPase (α3 NKA) is one of four known α isoforms of the mammalian transporter. A deficiency in α3 NKA is linked to severe movement control disorders. Understanding the pathogenesis of these disorders is limited by an incomplete knowledge of α3 NKA expression in the brain as well as the challenges associated with identifying living cells that express the isoform for subsequent electrophysiological studies. To address this problem, transgenic mice were generated on the C57BL/6 genetic background, which utilize the mouse α3 subunit gene ( Atp1a3 ) promoter to drive the expression of ZsGreen1 fluorescent protein. Consistent with published results on α3 NKA distribution, a ZsGreen1 signal was detected in the brain, but not in the liver, with Atp1a3-ZsGreen1 transgenic mice. The intensity of ZsGreen1 fluorescence in neuronal cell bodies varied considerably in the brain, being highest in the brainstem, deep cerebellar and select thalamic nuclei, and relatively weak in cortical regions. Fluorescence was not detected in astrocytes or white matter areas. ZsGreen1-positive neurons were readily observed in fresh (unfixed) brain sections, which were amenable to patch-clamp recordings. Thus, the α3 NKA-ZsGreen1 mouse model provides a powerful tool for studying the distribution and functional properties of α3 NKA-expressing neurons in the brain.